Evaluation of skills and tactics based on TOPSIS in table tennis - Zhao, Y. (International Journal of Table Tennis Sciences, 2013)
The author set up the skills and tactics evaluation system of table tennis. It is based on data collected from Zhang Jike`s 14 matches, using the TOPSIS method to calculate each match`s closing degree from positive and negative ideal solutions. According to these closing degrees, the research compares and analyses the whole series of matches. The results indicate there is a certain practicability in the assessment index system and assessing model.